A critical theoretical framework on participatory video in development communication - Mendoza, Trina Leah T. (The Philippine Journal of Development Communication, 2016)
This paper attempts to provide a critical theoretical framework on participatory video (PV) in development communication. It analyzes and defines the key concepts that are crucial in participatory video, namely, participation, meaning making, and empowerment. Ideally, community participants should reach the level of empowerment participation in the PV process, wherein they are considered as equal partners and they can control, own and make decisions on the process. PV aims to provide an alternative view of the world and enable community members, through critical and liberating dialogue throughout the different aspects of PV production to reflect, create meaning together, take action, and be empowered to create change in their lives. PV is an important tool, process, and praxis to help the marginalized or oppressed - through empowerment participation, critical meaning making, and empowerment - realize for themselves the issues and injustices that face and take action to free themselves from these conditions.